Honey market in the context of Turkey-European Union Relations: transition to organic beekeeping - Baytaroğlu, Adil (My University, 2006)
Tarımsal üretimde verim artırmak için kullanılan yapay ve kimyasal katkı maddeleri insan sağlığına zararlıdır. Bu katkı maddeleri ayrıca çevre üzerinde kalıcı etkisi uzun yıllar devam eder, yeraltı su kaynakları ve çevre kirliliğine neden olmaktadır. Yapay katkı maddeleri kulllanmadan yapılan organik tarımsal üretim giderek önem kazanmaya başlamıştır. Organik üretim tamamen kontrollu ve sertifikalı üretim şekli olup elde edilen ürünün kalitesi dünya’da kabul görmektedir. Bu konuda en büyük pazar olan Avrupa Birliği’nin izlenmesi önemlidir. Ülkemizin pazar payını koruması ancak kaliteli üretimle mümkün olabildiği saptanmıştır. Arıcılık ve bal sektörü ülkemizde ve Avrupa Birliği’nde ele alınmış ve tarımsal üretimdeki yeri anlatılmıştır. Üretim şekli ve gerekli teknik bilgilerde yer almaktadır. Ülkemiz ve Avrupa Birliği’nde arıcılık sektörünün yapısı , pazar payları , balın depolanması , satış kanalları, dış ticaretteki yeri, sorunları, ilgili yönetmelik ve tebliğler ve devlet destekleri gibi konular ele alınmıştır. Organik balın organik tarım ürünlerindeki yeri ve normal tarımın organik tarıma oranı gibi değerlendirmeler yapılmıştır. Yıllık büyüme oranları hesaplanmış gelecekteki dış ticaret payları ve ekonomideki yeri üzerinde bahsedilmiştir. Ülkemizin pazar payı üretimine göre düşük olduğu gözlenmiştir. Dünya organik tarım pazarının en az üç dört kat büyüyeceği tahmin edilmektedir. Arıcılık sektörü iktisadi açıdan değerlendirilmiştir. İktisadi temele göre incelendiğinden ekonomik veriler ve rakamlar üzerinde özellikle durulmuştur. Genellemeler yapılarak rekabet edebilirliği incelenmiştir. Teknik konulardan ziyade iktisadi meselelerle sonuca ulaşılmaya çalışılmıştır. Ayrıca verimlilik ve güçlü arı ırkı seçimi üzerinde durulmuştur. Ülkemizde koloni başına verim düşüktür. Organik arıcılığa geçiş özellikle ülkemiz arıcılık sektörünün satış ve pazarlama kabiliyetini geliştirecektir. Elde edilen ürünün sertifikalı olması ülkemiz arıcılık sektörüne pazarlama ve kalite avantajıda sağlamaktadır.

Artificial and chemical additives that are used in production to increase the productivity are harmful to the human health. These additives and its effects on environment continue for long years and also lead to the pollution of underground water resources and environmental pollution. Organic production that is performed without artificial additives is started to gaining a great importance. Organic production is totally controlled and certified kind of production method and the quality of the products which are harvested have been recognized in the world. Surveillance of European Union that is the biggest market in this field is very crucial. It has been observed that to protect of our country’s market share would only be possible with qualified production. Beekeeping and honey sector is taken into consideration both in our country and European Union and explained its place in agricultural production. The way of production and required technical data is also included. The structure of beekeeping sector both in our country and in European Union, the matters such as, market share, storage of honey, sales channels, its place in foreign trade, its problems, related directives and regulations and governmental supports are conveyed. The place of organic honey in agricultural products and proportion of conventional agriculture to organic agriculture are also considered. Yearly expansion rate are calculated, its market share in the future and its place in the economy are pointed. It is observed that our country’s market share is low compared to the production. Predictions are that global organic agricultural market will grow three to four times at least. Honey sector is evaluated from financial point. Because it is interpreted on economical basis, economical data and figures are handled specifically. Generalizations are used to investigate competitiveness. Economical matters, rather than technical subjects are discussed to end up with a conclusion. Besides, the productivity and strong bee strains selection are stated. Productivity per beehive in our country is low. Transition to organic beekeeping will improve marketing and sales ability of our country's honey sector. The acquired products with certification will provide marketing and quality advantage to our country’s beekeeping sector.
Keywords: Arıcılık_Pazarlama; Organik Tarım; Türkiye_Ekonomi_Avrupa Birliği